The three levels of the urban digital divide: bridging issues of coverage, usage and its outcomes in VGI platforms - Ferreira, Daniela (2021)
This article aims to provide a more detailed conception of the production of urban digital divides by VGI platforms in the context of the platform economy, through the articulation of the first (access and coverage), second (usage and skills) and third (outcomes) level of the digital divide. Our conceptual approach departs from a discussion of the geographical consequences of the different levels of the digital divide, focusing on their application to the study of VGI platforms, especially those working under the logic of the platform economy. We draw on a multi-level case study of the geographies of TripAdvisor and the geographies of restaurants or similar establishments in Lisbon, which comprised data analysis and interviews with restaurant owners, to argue that VGI platforms are producing urban digital divides that can only be fully detected through the triangulation of the different levels of the digital divide. They are not only producing different levels of territorial coverage in cities, but also different levels of usage intensity which have caused negative and positive outcomes for the firms associated. All these levels are spatially distributed, and such distribution is even more pronounced at a finer scale. We conclude that VGI platforms are producing a myriad of new forms of spatial divides that need more attention, given that the digital divide is present within the mechanisms designed by digital platforms. The vast and complex effects of such data engineering is best captured when all three levels of the digital divide are taken into account.